Pengaturan Ganti Kerugian Dalam Pengadaan Tanah Berdasarkan Undang-Undang No. 2 Tahun 2012 - Saniah Saniah (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
The objective of the research was to find out the regulation on compensation for land acquisition for publik interest, based of Law No. 2/2012. The juridicial sources were primary, secondary, and tertiary legal materials. The data were gathered by conducting documentary study. The research used juridical normative and prescriptive approach. The conclusion of the research was that Law No. 2/2012 regulated compensation for physical and non-physical loss even though the compensation for non-physical loss was too limited. Remaining property could not be classified or grouped into non-physical loss.